2012
DOI: 10.1149/2.016302jes
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Voltammetric Experiment - Simulation Comparisons of the Complex Mechanism Associated with Electrochemical Reduction of Zr4+in LiCl-KCl Eutectic Molten Salt

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
(39 reference statements)
1
12
0
1
Order By: Relevance
“…Lee et al [7] proposed a three step reduction mechanism whose redox couples are: Zr (IV)/Zr (II); Zr (II)/Zr and Zr(I)/Zr. Other authors showed a two step reduction mechanism whose redox couples differ [6,8,9]. For the first step, the authors agree on the reaction:…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Lee et al [7] proposed a three step reduction mechanism whose redox couples are: Zr (IV)/Zr (II); Zr (II)/Zr and Zr(I)/Zr. Other authors showed a two step reduction mechanism whose redox couples differ [6,8,9]. For the first step, the authors agree on the reaction:…”
Section: Introductionmentioning
confidence: 88%
“…a combination of two reactions: ZrðIVÞ þ 4e À $Zrð0Þ and ZrðIVÞ þ Cl À þ 3e À $ZrCl for Sakamura et al [8]. a combination of three reactions: ZrðIIÞ þ 2e À $Zrð0Þ, ZrðIVÞ þ 4e À $Zrð0Þ and ZrðIVÞ þ Cl À þ 3e À $ZrCl for Fabian et al [9].…”
Section: Introductionunclassified
“…Although the experimental system is LiCl-KCl-ZrCl 4 , electrochemical behaviors of zirconium ions are quite different due to differences in experimental temperature, concentration of zirconium ions, or the electrode material. It is generally believed that Zr(IV) will directly converted to Zr (II) without Zr(III), [14][15][16][17][18][19][20][21][22] while H. L. Cha 23 confirmed the formation of Zr(III) by XPS and square wave voltammetry.…”
mentioning
confidence: 99%
“…Factors such as temperature, concentration of zirconium, salt composition have been considered. In chloride-based salt mixtures such as LiCl-KCl-ZrCl 4 , 2,4,[7][8][9][10][11][12][13][14][15][16][17] NaCl-KCl-ZrCl 4 , 18 NaCl-ZrCl 4 , 8 it was believed that the reduction of Zr(IV) followed a multi-step mechanism, two soluble states of Zr(IV) and Zr(II) and two insoluble states of Zr(I) and Zr were confirmed. In fluoride-based salt mixtures, the reduction was thought to be less complicated, a single-step reduction of Zr(IV) to Zr(0) was approved in LiF-NaF-ZrF 4 , 19 LiF-CaF 2 -ZrF 4 , 20 and LiF-KF-ZrF 4 , 21 and a two-step reduction was endorsed in LiF-NaF-K 2 ZrF 6 , 22 LiF-KF-ZrF 4 .…”
mentioning
confidence: 99%